Association between physical performance and cardiovascular events in patients with coronary artery disease: protocol for a meta-analysis. Issue 1 (December 2016) - Yamamoto, Shuhei; Yamaga, Takayoshi; Sakai, Yasunari; Ishida, Takaaki; Nakasone, Saki; Ohira, Masayoshi; Ota, Erika; Mori, Rintaro
Abstract Background Physical performance such as muscle strength or walking speed of patients with coronary artery disease (CAD) is lower than that of people who do not have CAD and is related to mortality and re-admission rates. Recent studies have shown that skeletal muscle strength, such as grip strength, was closely associated with cardiac events. Physical performance testing is quick, safe, and inexpensive and provides a reliable assessment tool for routine clinical practice. The aim of this meta-analysis is to clarify the association between physical performance testing and the risk of cardiovascular events and mortality. Methods/design This meta-analysis will include male and female participants of any age in community settings who have a history of the following conditions or procedures: myocardial infarction, or coronary revascularization (coronary artery bypass grafting, percutaneous transluminal coronary angioplasty, or coronary artery stent), angina pectoris, heart failure, heart transplant, or coronary artery disease defined by angiography. We will search EMBASE and MEDLINE, PubMed, and the Cochrane Library with no limitations on date, language, document type, or publication status. Identified studies will be prospective and retrospective cohort studies. Physical performance will be defined as upper extremity strength, lower extremity strength, walking speed, or other performance scale. Six review authors will independently extract study characteristics from included studies. Participants will be divided into subgroups according to age (middle-aged <65 years and elderly ≥65 years), diagnosis (coronary artery disease and heart failure) and follow-up time (up to 12 months and over 12 months). We will pool hazard ratios of Cox proportional hazard models after logarithmic transformation and perform the meta-analysis by using inverse-variance method. Discussion To our knowledge, this meta-analysis will be the first report to assess the association between physical performance and cardiovascular events in CAD patients. We hope that these findings may help to estimate the prognosis for CAD patients in clinical practice. Systematic review registration PROSPEROCRD42015020886 .